Novel composite oxygen production molecular sieve capable of releasing negative oxygen ions and preparation method thereof
A novel composite molecular sieve is prepared by modifying tourmaline powder with Ce and La, then combining it with LSX molecular sieve and attapulgite clay, and exchanging with LiCl to produce a sieve that efficiently releases negative oxygen ions, addressing the deficiency of existing sieves and enhancing air purification.
Patent Information
- Application Number
- CN202411060894.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-13
AI Technical Summary
Existing molecular sieves, such as Li-LSX, do not have the capability to generate negative oxygen ions, and there is a lack of research on using tourmaline and LSX molecular sieves to address this deficiency.
A novel composite oxygen-generating sieve is prepared by first grinding tourmaline powder, mixing it with 2 times the volume of deionized water and stirring for 20-40 minutes, then adding Ce(NO3)3·6H2O and La(NO3)3·6H2O solutions, followed by ammonia water to adjust pH, and calcining at 700°C. The modified tourmaline powder is then ultrafine ground with sodium polyacrylate and melamine as dispersants, mixed with LSX molecular sieve powder and attapulgite clay, and exchanged with LiCl to produce a composite molecular sieve capable of releasing negative oxygen ions.
The composite molecular sieve effectively releases negative oxygen ions, enhancing air purification by neutralizing positive ions and absorbing harmful gases, while meeting radiation safety standards.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional molecular sieve preparation, and in particular to a novel composite oxygen-generating molecular sieve capable of releasing negative oxygen ions and a preparation method thereof. Background Art
[0002] Air pollution is one of the common environmental pollution problems faced by humans and urgently needs to be solved. The sources of pollutants in the air mainly include dust particles, exhaust gas emissions, and suspended microorganisms. Most of them carry positive ions. Too many positive ions can make the human body susceptible to respiratory diseases or induce various sub-health conditions. Air negative ions, also known as negative oxygen ions, are oxygen molecules in the air that gain excess electrons and become negatively charged oxygen ions. Negative oxygen ions have a positive effect on human health and environmental protection. Negative oxygen ions can combine with bacteria, smoke and other particles in the air to make them settle, and can also absorb harmful volatile gases such as formaldehyde to achieve the purpose of air crystallization.
[0003] Tourmaline can ionize water molecules and affect the structure of water. It has the characteristics of releasing negative oxygen ions and purifying the air. The negative oxygen ions released by tourmaline can not only neutralize the positive ions in the air, but also effectively interact with the odor source molecules attached to the walls and ceilings, so that the odor is no longer generated, thereby playing a role in purifying the environment. Tourmaline does not produce ozone, active oxygen and other substances that are harmful to the human body in the process of producing negative oxygen ions, so it is widely favored by people.
[0004] As an important raw material, oxygen has been widely used in chemical industry, environmental protection and national defense. At the same time, high-purity oxygen has also been widely used in metallurgy, medicine and other fields. At present, the molecular sieves used in oxygen generators on the market are mainly Li-LSX molecular sieves, which do not have the function of generating negative oxygen ions. There are also few research reports on the use of tourmaline and Li-LSX molecular sieves to prepare new molecular sieves that can release negative oxygen ions. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a novel composite oxygen-generating molecular sieve capable of releasing negative oxygen ions and a preparation method thereof.
[0007] (II) Technical solution
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] The present invention provides a novel composite oxygen-generating molecular sieve capable of releasing negative oxygen ions. The molecular sieve is prepared according to the following steps:
[0010] (1) using a ball mill to wet-grind the tourmaline raw material to obtain tourmaline powder, wherein the specific conditions are: a ball-to-material ratio of 1:3-5, anhydrous ethanol as a grinding solvent, mullite as a ball-milling medium, a slurry concentration of 60-70%, a filling rate of more than 70%, a temperature below 20° C., and grinding for more than 30 minutes to obtain tourmaline powder with a particle size of 5-8 μm;
[0011] (2) Mixing tourmaline powder with 2 times the volume of deionized water and stirring for 20-40 minutes, and ultrasonicating for 10-20 minutes to form a slurry; then dropping 0.05-0.1 mol / L Ce(NO3)3·6H2O solution and 0.01-0.05 mol / L La(NO3)3·6H2O solution into the slurry, and continue stirring for more than 2 hours at below 20°C to obtain a suspension; dropping ammonia water into the suspension to adjust the pH, stirring for 30-40 minutes, and then standing overnight. After complete precipitation, filtering, and washing with deionized water to pH≈7; drying the washed solid, calcining at 700°C for 4-5 hours, and cooling to room temperature to obtain modified tourmaline powder;
[0012] (3) using a ball mill to wet-grind the modified tourmaline powder to obtain ultrafine modified tourmaline powder, wherein the specific conditions are: a ball-to-material ratio of 1:4-6, anhydrous ethanol as a grinding solvent, sodium polyacrylate and melamine as dispersants, zirconium oxide as a ball-grinding medium, a slurry concentration of 60-65%, a filling rate of more than 65%, a temperature below 30° C., and grinding for more than 40 minutes to obtain an ultrafine modified tourmaline powder with a particle size of 0.7-2.5 μm;
[0013] (4) adding sodium hydroxide solution and potassium hydroxide solution to sodium aluminate solution respectively, stirring and mixing evenly, slowly adding water glass and deionized water dropwise under high-speed stirring, continuing stirring until it becomes a gel, aging at 30-40° C. for more than 24 hours to obtain a mixture 1, which is set aside;
[0014] (5) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 8-12 hours; and crystallization is performed at 90-100° C. for 2-4 hours to obtain LSX molecular sieve powder;
[0015] (6) Mechanically mixing LSX molecular sieve powder, ultrafine modified tourmaline powder, and attapulgite clay in a weight ratio of 8:0.1-0.5:0.5-1.5, adding water to granulate, and calcining the formed molecular sieve sample to obtain an LSX molecular sieve body;
[0016] (7) The LSX molecular sieve body is mixed with 1-2 mol / L LiCl solution at a solid-liquid ratio of 1:30, sealed and placed below 80°C, stirred for more than 30 minutes, then allowed to stand for 2-3 hours, vacuum filtered, and the exchange is repeated 5-7 times under the same conditions. After the exchange is completed, it is placed at 150°C and dried for more than 3 hours to obtain a new composite molecular sieve product that can release negative oxygen ions.
[0017] Specifically, in step (2), the contents of Ce and La in the modified tourmaline powder are 1-5% and 1-3%, respectively.
[0018] Specifically, in step (3), the amount of sodium polyacrylate added is 0.5-1.5% of the modified tourmaline powder, and the amount of melamine added is 0.1-0.5% of the modified tourmaline powder.
[0019] Specifically, in step (4), the molar ratios of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water are: Si2O / Al2O3=3-6:1, NaK / Si=2-4:1, Na / NaK=0.5-1:1, H2O / NaK=20-30:1.
[0020] Specifically, the addition amount of mixture 1 in step (5) is 6-8%; the molar ratios of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water are: Si2O / Al2O3=1-3:1, NaK / Si=2-4:1, Na / NaK=0.5-1:1, H2O / NaK=25-30:1.
[0021] Specifically, the calcination conditions in step (6) are: heating from room temperature to 100 degrees Celsius, maintaining for 20 minutes; then heating to 300°C, maintaining for 40 minutes; then heating to 400°C, maintaining for 1 hour; and finally heating to 500°C, maintaining for 3 hours.
[0022] The internal radiation equivalent and external radiation equivalent of the molecular sieve provided by the present invention are both less than 0.2 mSv, which meets the relevant national standards.
[0023] (III) Beneficial effects
[0024] The present invention provides a novel composite oxygen-generating molecular sieve capable of releasing negative oxygen ions and a preparation method thereof. The preparation method provided by the present invention is to grind the raw tourmaline powder first, obtain tourmaline powder with a smaller particle size, and then modify it with Ce and La to obtain modified tourmaline powder, and at the same time, perform ultrafine treatment on the modified tourmaline powder again to obtain ultrafine modified tourmaline powder, and reduce the particle size of the tourmaline raw material to increase the contact area with Ce and La, and increase the adhesion amount of Ce and La, and then perform the secondary ultrafine treatment process, through the grinding force, Ce and La are tightly combined with tourmaline to enhance the interaction between the two, while reducing the particle size of the modified tourmaline powder to a minimum, reducing its influence on the pores of the molecular sieve; in the preparation process of the molecular sieve, we adopt the method of mixing LSX powder with ultrafine modified tourmaline powder to obtain a molecular sieve body, and then perform Li exchange, the purpose of which is to ensure the adsorption performance of the molecular sieve, and finally obtain a novel composite Li-LSX type oxygen-generating molecular sieve capable of efficiently releasing negative oxygen ions. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] A novel composite oxygen-generating molecular sieve capable of releasing negative oxygen ions is prepared according to the following steps:
[0028] (1) using a ball mill to wet-grind the tourmaline raw material to obtain tourmaline powder, wherein the specific conditions are: a ball-to-material ratio of 1:3, anhydrous ethanol as a grinding solvent, mullite as a ball-milling medium, a slurry concentration of 70%, a filling rate of more than 70%, a temperature below 20° C., and grinding for more than 30 minutes to obtain tourmaline powder with a particle size of 5-8 μm;
[0029] (2) Mixing tourmaline powder with 2 times the volume of deionized water and stirring for 30 minutes, and ultrasonicating for 15 minutes to form a slurry; then dropping 0.05 mol / L Ce(NO3)3·6H2O solution and 0.03 mol / L La(NO3)3·6H2O solution into the slurry, and continuing to stir for more than 2 hours at below 20°C to obtain a suspension; dropping ammonia water into the suspension to adjust the pH, stirring for 30 minutes, and then standing overnight, after complete precipitation, filtering, and washing with deionized water to pH≈7; drying the washed solid, calcining at 700°C for 4-5 hours, and cooling to room temperature to obtain modified tourmaline powder; the contents of Ce and La in the modified tourmaline powder account for 4% and 1%, respectively;
[0030] (3) using a ball mill to wet-grind the modified tourmaline powder to obtain ultrafine modified tourmaline powder, wherein the specific conditions are as follows: the ball-to-material ratio is 1:4, anhydrous ethanol is used as a grinding solvent, sodium polyacrylate and melamine are used as dispersants, zirconium oxide is used as a ball-grinding medium, the slurry concentration is 65%, the filling rate is above 65%, the temperature is below 30° C., and the grinding time is more than 40 minutes to obtain ultrafine modified tourmaline powder with a particle size of 0.7-2.5 μm; the addition amount of sodium polyacrylate is 0.8% of the modified tourmaline powder, and the addition amount of melamine is 0.2% of the modified tourmaline powder;
[0031] (4) adding sodium hydroxide solution and potassium hydroxide solution to sodium aluminate solution respectively, stirring and mixing evenly, slowly adding water glass and deionized water dropwise under high-speed stirring, continuing stirring until it becomes a gel, aging at 40° C. for more than 24 hours, and obtaining a mixture 1 for standby use; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=3:1, NaK / Si=2:1, Na / NaK=0.5:1, H2O / NaK=20:1;
[0032] (5) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 10 hours; crystallization is performed at 100° C. for 3 hours to obtain LSX molecular sieve powder; the addition amount of mixture 1 is 6%; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=1.8:1, NaK / Si=2.5:1, Na / NaK=0.8:1, H2O / NaK=25:1;
[0033] (6) The LSX molecular sieve powder, ultrafine modified tourmaline powder and attapulgite clay were mechanically mixed in a weight ratio of 8:0.5:1.5, and water was added to granulate. The formed molecular sieve sample was calcined to obtain an LSX molecular sieve body; the calcination conditions were: heating from room temperature to 100 degrees Celsius and maintaining for 20 minutes; then heating to 300 degrees Celsius and maintaining for 40 minutes; then heating to 400 degrees Celsius and maintaining for 1 hour; finally heating to 500 degrees Celsius and maintaining for 3 hours.
[0034] (7) The LSX molecular sieve body was mixed with 1.2 mol / L LiCl solution at a solid-liquid ratio of 1:30, sealed and placed below 80°C, stirred for more than 30 minutes, then allowed to stand for 2-3 hours, vacuum filtered, and the exchange was repeated 5-7 times under the same conditions. After the exchange was completed, it was placed at 150°C and dried for more than 3 hours to obtain a new composite molecular sieve product that can release negative oxygen ions.
[0035] Example 2
[0036] A novel composite oxygen-generating molecular sieve capable of releasing negative oxygen ions is prepared according to the following steps:
[0037] (1) using a ball mill to wet-grind the tourmaline raw material to obtain tourmaline powder, wherein the specific conditions are: a ball-to-material ratio of 1:5, anhydrous ethanol as a grinding solvent, mullite as a ball-milling medium, a slurry concentration of 60%, a filling rate of more than 70%, a temperature below 20° C., and grinding for more than 30 minutes to obtain tourmaline powder with a particle size of 5-8 μm;
[0038] (2) Mixing tourmaline powder with 2 times the volume of deionized water and stirring for 40 minutes, and ultrasonicating for 20 minutes to form a slurry; then dropping 0.1 mol / L Ce(NO3)3·6H2O solution and 0.05 mol / L La(NO3)3·6H2O solution into the slurry, and continuing to stir for more than 2 hours at below 20°C to obtain a suspension; dropping ammonia water into the suspension to adjust the pH, stirring for 30-40 minutes, and then standing overnight, after complete precipitation, filtering, and washing with deionized water to pH≈7; drying the washed solid, calcining at 700°C for 4-5 hours, and cooling to room temperature to obtain modified tourmaline powder; the contents of Ce and La in the modified tourmaline powder account for 3% and 1.5%, respectively;
[0039] (3) using a ball mill to wet-grind the modified tourmaline powder to obtain ultrafine modified tourmaline powder, wherein the specific conditions are as follows: the ball-to-material ratio is 1:6, anhydrous ethanol is used as a grinding solvent, sodium polyacrylate and melamine are used as dispersants, zirconium oxide is used as a ball-grinding medium, the slurry concentration is 60%, the filling rate is above 65%, the temperature is below 30° C., and the grinding time is more than 40 minutes to obtain ultrafine modified tourmaline powder with a particle size of 0.7-2.5 μm; the amount of sodium polyacrylate added is 1.2% of the modified tourmaline powder, and the amount of melamine added is 0.2% of the modified tourmaline powder;
[0040] (4) Add sodium hydroxide solution and potassium hydroxide solution to sodium aluminate solution respectively, stir and mix evenly, slowly add water glass and deionized water dropwise under high-speed stirring, continue stirring until it becomes a gel, age at 30-40° C. for more than 24 hours, and obtain mixture 1 for standby use; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=6:1, NaK / Si=2.5:1, Na / NaK=0.7:1, H2O / NaK=25:1
[0041] (5) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 8-12 h; crystallization is performed at 90-100° C. for 2-4 h to obtain LSX molecular sieve powder; the addition amount of mixture 1 is 6.5%; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=2.4:1, NaK / Si=2:1, Na / NaK=0.7:1, H2O / NaK=30:1
[0042] (6) The LSX molecular sieve powder, ultrafine modified tourmaline powder and attapulgite clay were mechanically mixed in a weight ratio of 8:0.3:1.2, and water was added to granulate. The formed molecular sieve sample was calcined to obtain an LSX molecular sieve body; the calcination conditions were: heating from room temperature to 100 degrees Celsius and maintaining for 20 minutes; then heating to 300 degrees Celsius and maintaining for 40 minutes; then heating to 400 degrees Celsius and maintaining for 1 hour; finally heating to 500 degrees Celsius and maintaining for 3 hours.
[0043] (7) The LSX molecular sieve body was mixed with 1.5 mol / L LiCl solution at a solid-liquid ratio of 1:30, sealed and placed below 80°C, stirred for more than 30 minutes, then allowed to stand for 2-3 hours, vacuum filtered, and the exchange was repeated 5-7 times under the same conditions. After the exchange was completed, it was placed at 150°C and dried for more than 3 hours to obtain a new composite molecular sieve product that can release negative oxygen ions.
[0044] Example 3
[0045] A novel composite oxygen-generating molecular sieve capable of releasing negative oxygen ions is prepared according to the following steps:
[0046] (1) using a ball mill to wet-grind the tourmaline raw material to obtain tourmaline powder, wherein the specific conditions are: a ball-to-material ratio of 1:4, anhydrous ethanol as a grinding solvent, mullite as a ball-milling medium, a slurry concentration of 65%, a filling rate of more than 70%, a temperature below 20° C., and grinding for more than 30 minutes to obtain tourmaline powder with a particle size of 5-8 μm;
[0047] (2) Mixing tourmaline powder with 2 times the volume of deionized water and stirring for 35 minutes, and ultrasonicating for 15 minutes to form a slurry; then dropping 0.08 mol / L Ce(NO3)3·6H2O solution and 0.02 mol / L La(NO3)3·6H2O solution into the slurry, and continuing to stir for more than 2 hours at below 20°C to obtain a suspension; dropping ammonia water into the suspension to adjust the pH, stirring for 30-40 minutes, and then standing overnight, after complete precipitation, filtering, and washing with deionized water to pH≈7; drying the washed solid, calcining at 700°C for 4-5 hours, and cooling to room temperature to obtain modified tourmaline powder; the contents of Ce and La in the modified tourmaline powder are 2.5% and 1%, respectively;
[0048] (3) Using a ball mill to wet-grind the modified tourmaline powder to obtain ultrafine modified tourmaline powder, the specific conditions are: the ball-to-material ratio is 1:5, anhydrous ethanol is used as a grinding solvent, sodium polyacrylate and melamine are used as dispersants, zirconium oxide is used as a ball milling medium, the slurry concentration is 60-65%, the filling rate is above 65%, and the temperature is below 30° C., and the grinding time is more than 40 minutes to obtain ultrafine modified tourmaline powder with a particle size of 0.7-2.5 μm; the amount of sodium polyacrylate added is 1% of the modified tourmaline powder, and the amount of melamine added is 0.3% of the modified tourmaline powder.
[0049] (4) Sodium hydroxide solution and potassium hydroxide solution are added to sodium aluminate solution respectively, and the mixture is stirred and evenly mixed. Water glass and deionized water are slowly added dropwise under high-speed stirring, and the stirring is continued until it becomes a gel. The mixture is aged at 35° C. for more than 24 hours to obtain a mixture 1 for standby use. The molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=5.5:1, NaK / Si=3.6:1, Na / NaK=0.65:1, H2O / NaK=26:1
[0050] (5) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 8-12 h; crystallization is performed at 90-100° C. for 2-4 h to obtain LSX molecular sieve powder; the addition amount of mixture 1 is 7%; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=2.4:1, NaK / Si=2.4:1, Na / NaK=0.63:1, H2O / NaK=28:1.
[0051] (6) The LSX molecular sieve powder, ultrafine modified tourmaline powder and attapulgite clay were mechanically mixed in a weight ratio of 8:0.4:1.5, and water was added to granulate. The formed molecular sieve sample was calcined to obtain an LSX molecular sieve body; the calcination conditions were: heating from room temperature to 100 degrees Celsius and maintaining for 20 minutes; then heating to 300 degrees Celsius and maintaining for 40 minutes; then heating to 400 degrees Celsius and maintaining for 1 hour; finally heating to 500 degrees Celsius and maintaining for 3 hours.
[0052] (7) The LSX molecular sieve body is mixed with a 2 mol / L LiCl solution at a solid-liquid ratio of 1:30, sealed and placed below 80°C, stirred for more than 30 minutes, then allowed to stand for 2-3 hours, vacuum filtered, and the exchange is repeated 5-7 times under the same conditions. After the exchange is completed, it is placed at 150°C and dried for more than 3 hours to obtain a new composite molecular sieve product that can release negative oxygen ions.
[0053] Comparative Example 1
[0054] A molecular sieve is prepared according to the following steps:
[0055] (1) Using a ball mill to wet-grind a tourmaline raw material to obtain ultrafine modified tourmaline powder, the specific conditions are: the ball-to-material ratio is 1:4, anhydrous ethanol is used as a grinding solvent, sodium polyacrylate and melamine are used as dispersants, zirconium oxide is used as a ball milling medium, the slurry concentration is 65%, the filling rate is above 65%, the temperature is below 30° C., and the grinding time is more than 40 minutes to obtain an ultrafine tourmaline powder with a particle size of 0.7-2.5 μm; the addition amount of sodium polyacrylate is 0.8% of the modified tourmaline powder, and the addition amount of melamine is 0.2% of the tourmaline raw material;
[0056] (4) adding sodium hydroxide solution and potassium hydroxide solution to sodium aluminate solution respectively, stirring and mixing evenly, slowly adding water glass and deionized water dropwise under high-speed stirring, continuing stirring until it becomes a gel, aging at 40° C. for more than 24 hours, and obtaining a mixture 1 for standby use; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=3:1, NaK / Si=2:1, Na / NaK=0.5:1, H2O / NaK=20:1;
[0057] (5) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 10 hours; crystallization is performed at 100° C. for 3 hours to obtain LSX molecular sieve powder; the addition amount of mixture 1 is 6%; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=1.8:1, NaK / Si=2.5:1, Na / NaK=0.8:1, H2O / NaK=25:1;
[0058] (6) The LSX molecular sieve powder, ultrafine tourmaline powder and attapulgite clay were mechanically mixed in a weight ratio of 8:0.5:1.5, and water was added to granulate. The formed molecular sieve sample was calcined to obtain an LSX molecular sieve body; the calcination conditions were: heating from room temperature to 100 degrees Celsius and maintaining for 20 minutes; then heating to 300 degrees Celsius and maintaining for 40 minutes; then heating to 400 degrees Celsius and maintaining for 1 hour; finally heating to 500 degrees Celsius and maintaining for 3 hours.
[0059] (7) The LSX molecular sieve body was mixed with 1.2 mol / L LiCl solution at a solid-liquid ratio of 1:30, sealed and placed below 80°C, stirred for more than 30 minutes, then allowed to stand for 2-3 hours, vacuum filtered, and the exchange was repeated 5-7 times under the same conditions. After the exchange was completed, it was placed at 150°C and dried for more than 3 hours to obtain a molecular sieve product.
[0060] Comparative Example 2
[0061] A molecular sieve is prepared according to the following steps:
[0062] (1) using a ball mill to wet-grind the tourmaline raw material to obtain tourmaline powder, wherein the specific conditions are: a ball-to-material ratio of 1:3, anhydrous ethanol as a grinding solvent, mullite as a ball-milling medium, a slurry concentration of 70%, a filling rate of more than 70%, a temperature below 20° C., and grinding for more than 30 minutes to obtain tourmaline powder with a particle size of 5-8 μm;
[0063] (2) Mixing tourmaline powder with 2 times the volume of deionized water and stirring for 30 minutes, and ultrasonicating for 15 minutes to form a slurry; then dropping 0.05 mol / L Ce(NO3)3·6H2O solution and 0.03 mol / L La(NO3)3·6H2O solution into the slurry, and continuing to stir for more than 2 hours at below 20°C to obtain a suspension; dropping ammonia water into the suspension to adjust the pH, stirring for 30 minutes, and then standing overnight, after complete precipitation, filtering, and washing with deionized water to pH≈7; drying the washed solid, calcining at 700°C for 4-5 hours, and cooling to room temperature to obtain modified tourmaline powder; the contents of Ce and La in the modified tourmaline powder account for 4% and 1%, respectively;
[0064] (3) using a ball mill to wet-grind the modified tourmaline powder to obtain ultrafine modified tourmaline powder, wherein the specific conditions are as follows: the ball-to-material ratio is 1:4, anhydrous ethanol is used as a grinding solvent, sodium polyacrylate and melamine are used as dispersants, zirconium oxide is used as a ball-grinding medium, the slurry concentration is 65%, the filling rate is above 65%, the temperature is below 30° C., and the grinding time is more than 40 minutes to obtain ultrafine modified tourmaline powder with a particle size of 0.7-2.5 μm; the addition amount of sodium polyacrylate is 0.8% of the modified tourmaline powder, and the addition amount of melamine is 0.2% of the modified tourmaline powder;
[0065] (4) adding sodium hydroxide solution and potassium hydroxide solution to sodium aluminate solution respectively, stirring and mixing evenly, slowly adding water glass and deionized water dropwise under high-speed stirring, continuing stirring until it becomes a gel, aging at 40° C. for more than 24 hours, and obtaining a mixture 1 for standby use; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=3:1, NaK / Si=2:1, Na / NaK=0.5:1, H2O / NaK=20:1;
[0066] (5) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 10 hours; crystallization is performed at 100° C. for 3 hours to obtain LSX molecular sieve powder; the addition amount of mixture 1 is 6%; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=1.8:1, NaK / Si=2.5:1, Na / NaK=0.8:1, H2O / NaK=25:1;
[0067] (6) The LSX molecular sieve powder was mixed with 1.2 mol / L LiCl solution at a solid-liquid ratio of 1:30, sealed and placed below 80°C, stirred for more than 30 minutes, then allowed to stand for 2-3 hours, vacuum filtered, and the exchange was repeated 5-7 times under the same conditions. After the exchange was completed, it was placed at 150°C and dried for more than 3 hours to obtain Li-LSX molecular sieve powder.
[0068] (7) Li-LSX molecular sieve powder, ultrafine modified tourmaline powder and attapulgite clay are mechanically mixed in a weight ratio of 8:0.5:1.5, water is added to granulate, and the formed molecular sieve sample is calcined to obtain the molecular sieve product; the calcination conditions are: heating from room temperature to 100 degrees Celsius and maintaining for 20 minutes; then heating to 300°C and maintaining for 40 minutes; then heating to 400°C and maintaining for 1 hour; finally heating to 500°C and maintaining for 3 hours.
[0069] Comparative Example 3
[0070] A molecular sieve is prepared according to the following steps:
[0071] (1) Using a ball mill to wet-grind a tourmaline raw material to obtain ultrafine tourmaline powder, the specific conditions are: a ball-to-material ratio of 1:4, anhydrous ethanol as a grinding solvent, sodium polyacrylate and melamine as dispersants, zirconium oxide as a ball-grinding medium, a slurry concentration of 65%, a filling rate of more than 65%, a temperature below 30° C., and grinding for more than 40 minutes to obtain an ultrafine tourmaline powder with a particle size of 0.7-2.5 μm; the addition amount of sodium polyacrylate is 0.8% of the modified tourmaline powder, and the addition amount of melamine is 0.2% of the tourmaline raw material;
[0072] (2) adding sodium hydroxide solution and potassium hydroxide solution to sodium aluminate solution respectively, stirring and mixing evenly, slowly adding water glass and deionized water dropwise under high-speed stirring, continuing stirring until it becomes a gel, aging at 40° C. for more than 24 hours, and obtaining a mixture 1 for standby use; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=3:1, NaK / Si=2:1, Na / NaK=0.5:1, H2O / NaK=20:1;
[0073] (3) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 10 hours; crystallization is performed at 100° C. for 3 hours to obtain LSX molecular sieve powder; the addition amount of mixture 1 is 6%; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=1.8:1, NaK / Si=2.5:1, Na / NaK=0.8:1, H2O / NaK=25:1;
[0074] (6) Mix the LSX molecular sieve powder with a 1.2 mol / L LiCl solution at a solid-liquid ratio of 1:30, seal and place below 80°C, stir for more than 30 minutes, then stand for 2-3 hours, vacuum filter, repeat the exchange 5-7 times under the same conditions, and place at 150°C and dry for more than 3 hours after the exchange to obtain Li-LSX molecular sieve powder;
[0075] (7) Mixing Li-LSX molecular sieve powder with 0.05 mol / L Ce(NO3)3·6H2O solution and 0.03 mol / L La(NO3)3·6H2O solution at a solid-liquid ratio of 1:20, stirring for more than 20 min, standing at room temperature for more than 3 h, vacuum filtering, repeating the exchange three times under the same conditions, and drying at below 150° C. for more than 3 hours after the exchange, to obtain Ce / La-Li-LSX molecular sieve powder;
[0076] (8) Ce / La-Li-LSX molecular sieve powder, ultrafine tourmaline powder and attapulgite clay were mechanically mixed in a weight ratio of 8:0.5:1.5, water was added to granulate, and the formed molecular sieve sample was calcined to obtain the molecular sieve product; the calcination conditions were: heating from room temperature to 100 degrees Celsius and maintaining for 20 minutes; then heating to 300°C and maintaining for 40 minutes; then heating to 400°C and maintaining for 1 hour; finally heating to 500°C and maintaining for 3 hours.
[0077] Comparative Example 4
[0078] A molecular sieve is prepared according to the following steps:
[0079] (1) using a ball mill to wet-grind the tourmaline raw material to obtain tourmaline powder, wherein the specific conditions are: a ball-to-material ratio of 1:3, anhydrous ethanol as a grinding solvent, mullite as a ball-milling medium, a slurry concentration of 70%, a filling rate of more than 70%, a temperature below 20° C., and grinding for more than 30 minutes to obtain tourmaline powder with a particle size of 5-8 μm;
[0080] (2) Mixing tourmaline powder with 2 times the volume of deionized water and stirring for 30 minutes, and ultrasonicating for 15 minutes to form a slurry; then dropping 0.05 mol / L Ce(NO3)3·6H2O solution and 0.03 mol / L La(NO3)3·6H2O solution into the slurry, and continuing to stir for more than 2 hours at below 20°C to obtain a suspension; dropping ammonia water into the suspension to adjust the pH, stirring for 30 minutes, and then standing overnight, after complete precipitation, filtering, and washing with deionized water to pH≈7; drying the washed solid, calcining at 700°C for 4-5 hours, and cooling to room temperature to obtain modified tourmaline powder; the contents of Ce and La in the modified tourmaline powder account for 4% and 1%, respectively;
[0081] (3) adding sodium hydroxide solution and potassium hydroxide solution to sodium aluminate solution respectively, stirring and mixing evenly, slowly adding water glass and deionized water dropwise under high-speed stirring, continuing stirring until it becomes a gel, aging at 40° C. for more than 24 hours, and obtaining a mixture 1 for standby use; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=3:1, NaK / Si=2:1, Na / NaK=0.5:1, H2O / NaK=20:1;
[0082] (5) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 10 hours; crystallization is performed at 100° C. for 3 hours to obtain LSX molecular sieve powder; the addition amount of mixture 1 is 6%; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=1.8:1, NaK / Si=2.5:1, Na / NaK=0.8:1, H2O / NaK=25:1;
[0083] (6) The LSX molecular sieve powder, modified tourmaline powder and attapulgite clay were mechanically mixed in a weight ratio of 8:0.5:1.5, and water was added to granulate. The formed molecular sieve sample was calcined to obtain an LSX molecular sieve body; the calcination conditions were: heating from room temperature to 100 degrees Celsius and maintaining for 20 minutes; then heating to 300 degrees Celsius and maintaining for 40 minutes; then heating to 400 degrees Celsius and maintaining for 1 hour; finally heating to 500 degrees Celsius and maintaining for 3 hours.
[0084] (7) The LSX molecular sieve body is mixed with 1.2 mol / L LiCl solution at a solid-liquid ratio of 1:30, sealed and placed below 80°C, stirred for more than 30 minutes, then allowed to stand for 2-3 hours, vacuum filtered, and the exchange is repeated 5-7 times under the same conditions. After the exchange is completed, it is placed at 150°C and dried for more than 3 hours to obtain a Li-LSX molecular sieve product that can release negative oxygen ions.
[0085] Comparative Example 5
[0086] Li-LSX molecular sieve is prepared according to the following steps:
[0087] (1) adding sodium hydroxide solution and potassium hydroxide solution to sodium aluminate solution respectively, stirring and mixing evenly, slowly adding water glass and deionized water dropwise under high-speed stirring, continuing stirring until it becomes a gel, aging at 40° C. for more than 24 hours, and obtaining a mixture 1 for standby use; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=3:1, NaK / Si=2:1, Na / NaK=0.5:1, H2O / NaK=20:1;
[0088] (2) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 10 hours; crystallization is performed at 100° C. for 3 hours to obtain LSX molecular sieve powder; the addition amount of mixture 1 is 6%; the molar ratio of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water is: Si2O / Al2O3=1.8:1, NaK / Si=2.5:1, Na / NaK=0.8:1, H2O / NaK=25:1;
[0089] (3) The LSX molecular sieve powder and attapulgite clay were mechanically mixed in a weight ratio of 8:1.5, water was added to granulate, and the formed molecular sieve sample was calcined to obtain an LSX molecular sieve body; the calcination conditions were: heating from room temperature to 100 degrees Celsius, maintaining for 20 minutes; then heating to 300 degrees Celsius, maintaining for 40 minutes; then heating to 400 degrees Celsius, maintaining for 1 hour; finally heating to 500 degrees Celsius, maintaining for 3 hours;
[0090] (4) The LSX molecular sieve body was mixed with 1.2 mol / L LiCl solution at a solid-liquid ratio of 1:30, sealed and placed below 80°C, stirred for more than 30 minutes, then allowed to stand for 2-3 hours, vacuum filtered, and the exchange was repeated 5-7 times under the same conditions. After the exchange was completed, it was placed at 150°C and dried for more than 3 hours to obtain a Li-LSX molecular sieve product.
[0091] Test Example 1
[0092] Adsorption performance test
[0093] The adsorption of nitrogen and oxygen by the molecular sieve products of Example 1 and Comparative Examples 1-5 was measured by a vacuum adsorption device. The results are shown in Table 1. Compared with the Li-LSX molecular sieve (Comparative Example 5), the nitrogen adsorption and nitrogen-oxygen separation coefficients of the molecular sieve samples prepared in Example 1 and Comparative Examples 1-4 have a tendency to decrease. The reason for this may be that the addition of tourmaline has a certain influence on the pores of the molecular sieve, occupying part of the pore position, resulting in a decrease in the adsorption amount, but the nitrogen adsorption of each molecular sieve sample is above 19 mL / g, which meets the requirements of air separation oxygen enrichment. Compared with the samples of Comparative Examples 1-4, the different preparation methods of the molecular sieve samples in Example 1 also have a significant effect on the nitrogen adsorption and nitrogen-oxygen separation coefficients of the molecular sieve samples. The preparation method described in Example 1 can retain the original adsorption performance of the molecular sieve to a greater extent.
[0094] Table 1 Adsorption performance results of molecular sieve products of Example 1 and Comparative Examples 1-4
[0095] sample Nitrogen adsorption capacity (mL / g) <![CDATA[Separation coefficient of nitrogen and oxygen N2 / O2]]> Example 1 22.7 6.0 Comparative Example 1 21.4 5.8 Comparative Example 2 19.8 5.6 Comparative Example 3 20.0 6.0 Comparative Example 4 19.2 5.3 Comparative Example 5 25.9 6.4
[0096] Test Example 2
[0097] Negative oxygen ion release capacity test
[0098] Test method: The negative ion release test space of the material is V = 1m 3 The molecular sieve sample has a mass of 500 g and is laid flat so that its contact area is S = 0.5 m 2 The test time is 12h, the test conditions are normal temperature and pressure, humidity is 60%, the ion counter model is AN-500 air negative ion detector, purchased from Chongqing Annain Environmental Technology Co., Ltd., the resolution is 1 / cm3, and the measurement accuracy of negative oxygen ions is ±15%. The negative ion concentration test method is based on JC / T 2110-2012 "Indoor Air Ion Concentration Test Method".
[0099] Test samples: molecular sieve samples prepared in Examples 1-3 and Comparative Examples 1-4.
[0100] Test results: Table 2 shows the test results of the negative oxygen ion release capacity of the molecular sieves prepared in Examples 1-3 and Comparative Examples 1-4.
[0101] Compared with Example 1, the tourmaline used in Comparative Example 1 has not been modified by Ce and La, but the tourmaline raw material has been ultrafinely ground. The concentration of negative oxygen ions that can be released is reduced by nearly 1 times compared with Example 1. This result shows that in the present invention, rare earth oxides and tourmaline cooperate with each other, and the organic combination of the two can significantly enhance the ability of the molecular sieve to release negative oxygen ions.
[0102] Compared with Example 1, Comparative Example 2 is that Li-LSX molecular sieve powder is first obtained and then mixed with ultrafine modified tourmaline powder to obtain a molecular sieve body. However, the concentration of released negative oxygen ions in Comparative Example 2 is significantly lower than that in Example 1 and also lower than that in Comparative Example 1. This may be because the LSX molecular sieve powder is first Li-exchanged and then granulated into a molecular sieve body, which significantly reduces the adsorption capacity of the molecular sieve and the amount of oxygen that can be adsorbed in the pores, thereby reducing the available oxygen of the ultrafine modified tourmaline. In addition, the ultrafine modified tourmaline has an uneven mixing problem when mixed with the Li-LSX molecular sieve powder for granulation, which ultimately leads to a greatly reduced ability of the molecular sieve in Comparative Example 2 to release negative oxygen ions.
[0103] Compared with Example 1, Comparative Example 3 is that Li-LSX molecular sieve powder is modified with Ce and La to obtain Ce / La-Li-LSX molecular sieve powder, and then mixed with ultrafine tourmaline powder for granulation to obtain a molecular sieve body, and the concentration of released negative oxygen ions is also significantly lower than that of Example 1; the reason for this result may be that Ce and La are added to the Li-LSX molecular sieve powder in the form of exchange parts, there are problems such as low exchange amount, loose binding of ions and molecular sieve after exchange, the interaction between Ce and La and tourmaline is weakened, and at the same time, the adsorption performance of the molecular sieve is affected.
[0104] Compared with Example 1, the modified tourmaline powder used in Comparative Example 4 has not been subjected to ultrafine treatment, and the particle size is too large, which reduces the contact area with oxygen and reduces the efficiency of the modified tourmaline in releasing negative oxygen ions. In addition, when the modified tourmaline is mixed with the LSX molecular sieve powder to form a molecular sieve body for Li exchange, the Li exchange efficiency is significantly affected, and the adsorption performance of the molecular sieve is significantly reduced, which ultimately leads to a greatly reduced ability of Comparative Example 4 to release negative oxygen ions.
[0105] The molecular sieve prepared in Example 1-3 can release negative oxygen ions with a concentration of 40000 (S·cm 3) or more, and the ability to release negative oxygen ions is significantly better than that of comparative examples 1-4. The preparation method provided by the present invention is to grind the raw tourmaline powder first, obtain tourmaline powder with a smaller particle size, and then modify it with Ce and La to obtain modified tourmaline powder, and at the same time, the modified tourmaline powder is once again subjected to ultrafine treatment to obtain ultrafine modified tourmaline powder. The purpose of doing so is that reducing the particle size of the tourmaline raw material is conducive to increasing the contact area with Ce and La, and increasing the adhesion amount of Ce and La. Then, during the secondary ultrafine treatment, the force of grinding allows Ce and La to be tightly combined with tourmaline to enhance the interaction between the two, while reducing the particle size of the modified tourmaline powder to a minimum, thereby reducing its influence on the pores of the molecular sieve; in the preparation process of the molecular sieve, we adopt the method of mixing LSX powder with ultrafine modified tourmaline powder to obtain a molecular sieve body, and then performing Li exchange, the purpose of which is to ensure the adsorption performance of the molecular sieve, and finally obtain a new composite Li-LSX type molecular sieve that can release negative oxygen ions. Compared with Comparative Examples 1-4, the preparation method provided by the present invention is the best solution for making the prepared molecular sieve have high-efficiency negative oxygen ion release ability.
[0106] Table 2 Test results of negative oxygen ion release capacity of molecular sieves prepared in Examples 1-3 and Comparative Examples 1-4
[0107] sample <![CDATA[Negative oxygen ion concentration per (S·cm 3 )]]> Example 1 45600 Example 2 43250 Example 3 42600 Comparative Example 1 23950 Comparative Example 2 20500 Comparative Example 3 30250 Comparative Example 4 16250
[0108] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A novel composite oxygen-generating molecular sieve capable of releasing negative oxygen ions, characterized in that: The molecular sieve is prepared according to the following steps: (1) using a ball mill to wet-grind the tourmaline raw material to obtain tourmaline powder, wherein the specific conditions are: a ball-to-material ratio of 1:3-5, anhydrous ethanol as a grinding solvent, mullite as a ball-milling medium, a slurry concentration of 60-70%, a filling rate of more than 70%, a temperature below 20° C., and grinding for more than 30 minutes to obtain tourmaline powder with a particle size of 5-8 μm; (2) Mixing tourmaline powder with 2 times the volume of deionized water and stirring for 20-40 minutes, and ultrasonicating for 10-20 minutes to form a slurry; then dropping 0.05-0.1 mol / L Ce(NO3)3·6H2O solution and 0.01-0.05 mol / L La(NO3)3·6H2O solution into the slurry, and continue stirring for more than 2 hours at below 20°C to obtain a suspension; dropping ammonia water into the suspension to adjust the pH, stirring for 30-40 minutes, and then standing overnight. After complete precipitation, filtering, and washing with deionized water to pH≈7; drying the washed solid, calcining at 700°C for 4-5 hours, and cooling to room temperature to obtain modified tourmaline powder; (3) using a ball mill to wet-grind the modified tourmaline powder to obtain ultrafine modified tourmaline powder, wherein the specific conditions are: a ball-to-material ratio of 1:4-6, anhydrous ethanol as a grinding solvent, sodium polyacrylate and melamine as dispersants, zirconium oxide as a ball-grinding medium, a slurry concentration of 60-65%, a filling rate of more than 65%, a temperature below 30° C., and grinding for more than 40 minutes to obtain an ultrafine modified tourmaline powder with a particle size of 0.7-2.5 μm; (4) adding sodium hydroxide solution and potassium hydroxide solution to sodium aluminate solution respectively, stirring and mixing evenly, slowly adding water glass and deionized water dropwise under high-speed stirring, continuing stirring until it becomes a gel, aging at 30-40° C. for more than 24 hours to obtain a mixture 1, which is set aside; (5) Sodium aluminate, sodium hydroxide, potassium hydroxide and deionized water are stirred and mixed, water glass is added under high-speed stirring, and stirring is continued until it becomes a gel, and then mixture 1 is added and stirred evenly; aging is performed at above 65° C. for 8-12 hours; and crystallization is performed at 90-100° C. for 2-4 hours to obtain LSX molecular sieve powder; (6) Mechanically mixing LSX molecular sieve powder, ultrafine modified tourmaline powder, and attapulgite clay in a weight ratio of 8:0.1-0.5:0.5-1.5, adding water to granulate, and calcining the formed molecular sieve sample to obtain an LSX molecular sieve body; (7) The LSX molecular sieve body is mixed with 1-2 mol / L LiCl solution at a solid-liquid ratio of 1:30, sealed and placed below 80°C, stirred for more than 30 minutes, then allowed to stand for 2-3 hours, vacuum filtered, and the exchange is repeated 5-7 times under the same conditions. After the exchange is completed, it is placed at 150°C and dried for more than 3 hours to obtain a new composite molecular sieve product that can release negative oxygen ions.
2. A novel composite oxygen-producing molecular sieve capable of releasing negative oxygen ions according to claim 1, characterized in that: In step (2), the contents of Ce and La in the modified tourmaline powder are 1-5% and 1-3% respectively.
3. A novel composite oxygen-producing molecular sieve capable of releasing negative oxygen ions according to claim 1, characterized in that: In step (3), the amount of sodium polyacrylate added is 0.5-1.5% of the modified tourmaline powder, and the amount of melamine added is 0.1-0.5% of the modified tourmaline powder.
4. A novel composite oxygen-producing molecular sieve capable of releasing negative oxygen ions according to claim 1, characterized in that: In step (4), the molar ratios of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water are: Si2O / Al2O3=3-6:1, NaK / Si=2-4:1, Na / NaK=0.5-1:1, H2O / NaK=20-30:
1.
5. The novel composite oxygen-producing molecular sieve capable of releasing negative oxygen ions according to claim 1, characterized in that: In step (5), the addition amount of mixture 1 is 6-8%; the molar ratios of sodium aluminate, aluminum hydroxide, potassium hydroxide, water glass and deionized water are: Si2O / Al2O3=1-3:1, NaK / Si=2-4:1, Na / NaK=0.5-1:1, H2O / NaK=25-30:
1.
6. The novel composite oxygen-producing molecular sieve capable of releasing negative oxygen ions according to claim 1, characterized in that: The calcination conditions in step (6) are: heating from room temperature to 100 degrees Celsius and maintaining for 20 minutes; then heating to 300 degrees Celsius and maintaining for 40 minutes; then heating to 400 degrees Celsius and maintaining for 1 hour; and finally heating to 500 degrees Celsius and maintaining for 3 hours.
